Non-Small Cell Lung Cancer (NSCLC): An Update - Uddin, Dayem (TAJ: Journal of Teachers Association, 2009)
Non-Small Cell lung Cancer can be treated with survival benefit providing better quality of life by applying new chemotherapeutic dosing schemes. Though Surgery and Radiotherapy provide good results in non small cell lung cancer, most of the patients turn up to doctors in advanced stages where these facilities can not be offered properly. Combination chemotherapy with carboplatin or cisplatin with Taxotere and Gemcirabine is now a better option. Chemotherapy with carboplatin, Gemcirabine, Taxotere and Novelbine is also a better dosing schemes. doi: 10.3329/taj.v15i2.3923 TAJ December 2002; Vol.15(2): 115-118